Neogene evolution of the eastern margin of Gulf of California, Sonora, Mexico: Insights from low-temperature thermochronology. (November 2020) - Lugo-Zazueta, R.; Kohn, B.; Gleadow, A.; Calmus, T.; Ramos-Velázquez, E.; Fletcher, J.M.; Pérez-Segura, E.
Abstract: The rifted margin of Sonora in Mexico experienced the early stages of Neogene extension related to Gulf of California opening, when the Baja California peninsula was originally part of the North America plate. The early evolution considers that during the late Miocene the plate motion was accommodated in an initial stage known as the "proto-Gulf". Then, Pacific plate motion relative to the North America plate migrated progressively westwards with a transtensional deformation accommodated by a series of transform faults and pull-apart basins forming the present Gulf of California. New apatite fission track and apatite and zircon (U–Th)/He analyses were performed on granitoid outcrops from coastal and mainland Sonora and the southwestern flank of Isla Tiburón within the Gulf. These combined dating techniques cover a range of typical temperature sensitivities from ~185° to ~30 °C. Previous geochemistry, geochronology and the new thermochronology data from this study allow an interpretation involving three extensional stages. The earliest stage suggests that exhumation of these plutons occurred in a transitional extensional region, where extension began during Oligo-Miocene Basin and Range extension and followed during the Gulf of California opening. This region extends from the Guaymas and Empalme coastline to the Hermosillo region, to the north, and displays characteristic rapid cooling from ~13 to ~8 Ma. This transitional zone is characterized by an E-W extensional regime and occurrences of tholeiitic volcanism (10.3–8.5 Ma) along the flanks of the Empalme Graben. The second stage occurs in the Bahia Kino area and northern coastal region of Sonora where thermal histories suggest a phase of relatively rapid cooling between ~7 and ~5 Ma associated with NW-SE Gulf of California extension. This stage is supported independently by previously reported ages of faulted volcanic units in the Bahia Kino region. The third stage is defined along the southwestern margin of Tiburon island. Thermal histories indicate rapid cooling between ~5 Ma and ~3 Ma, which is related to deformation on the Tiburon transform fault. Lastly, deformation migrated at ~3 Ma to the Ballenas transform fault system and to other coeval transform faults and pull-apart basins within the Gulf of California. Highlights: Low temperature thermochronology applied to extensional tectonics. Thermal history reconstructions provided insights for tectonic evolution. Eastern margin of Gulf of California deformation migrated westwards from late Miocene.